Calcium Signaling, PKC Gamma, IP(3)R1 and CAR8 Link Spinocerebellar Ataxias and Purkinje Cell Dendritic Development - Shimobayashi, Etsuko (Curr Neuropharmacol, 2018)
BACKGROUND: Spinocerebellar ataxias (SCAs) are a group of cerebellar diseases characterized by progressive ataxia and cerebellar atrophy. Several forms of SCAs are caused by missense mutations or deletions in genes related to calcium signaling in Purkinje cells. Among them, spinocerebellar ataxia type 14 (SCA14) is caused by missense mutations in PRKCG gene which encodes protein kinase C gamma (PKCγ). It is remarkable that in several cases in which SCA is caused by point mutations in an individual gene, the affected genes are involved in the PKCγ signaling pathway and calcium signaling which is not only crucial for proper Purkinje cell function but is also involved in the control of Purkinje cell dendritic development. In this review, we will focus on the PKCγ signaling related genes and calcium signaling related genes then discuss their role for both Purkinje cell dendritic development and cerebellar ataxia. METHODS: Research related to SCAs and Purkinje cell dendritic development is reviewed. RESULTS: PKCγ dysregulation causes abnormal Purkinje cell dendritic development and SCA14. Carbonic anhydrase related protein 8 (Car8) encoding CAR8 and Itpr1 encoding IP3R1were identified as upregulated genes in one of SCA14 mouse model. IP3R1, CAR8 and PKCγ proteins are strongly and specifically expressed in Purkinje cells. The common function among them is that they are involved in the regulation of calcium homeostasis in Purkinje cells and their dysfunction causes ataxia in mouse and human. Furthermore, disruption of intracellular calcium homeostasis caused by mutations in some calcium channels in Purkinje cells links to abnormal Purkinje cell dendritic development and the pathogenesis of several SCAs. CONCLUSION: Once PKCγ signaling related genes and calcium signaling related genes are disturbed, the normal dendritic development of Purkinje cells is impaired as well as the integration of signals from other neurons, resulting in abnormal development, cerebellar dysfunction and eventually Purkinje cell loss.